2014
DOI: 10.1111/papt.12020
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive analytic therapy: A review of the outcome evidence base for treatment

Abstract: Purpose This study reviews the quality of the extant outcome evidence for cognitive analytic therapy (CAT) to inform clinical practice and to stimulate a future CAT research strategy. Method An electronic search identified CAT efficacy and effectiveness studies and these were subject to systematic review. The methodological quality of studies meeting inclusion criteria were appraised using two validated research study quality checklists and studies were fitted to an established model of psychotherapy evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 90 publications
7
45
0
Order By: Relevance
“…The rate (90%) of patients starting and completing full CAT-SH is evidence of a high treatment retention rate. This is in line with evidence that records low dropout rates across CAT outcome studies (albeit in high-intensity versions of the model; Calvert and Kellett, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…The rate (90%) of patients starting and completing full CAT-SH is evidence of a high treatment retention rate. This is in line with evidence that records low dropout rates across CAT outcome studies (albeit in high-intensity versions of the model; Calvert and Kellett, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…The majority of MBT published evidence was assessed to be of fair (43%) or good (34%) quality with very similar mean ratings for RCTs ( M = 20) and practice‐based effectiveness studies ( M = 16) to those reported by Calvert and Kellett () when assessing the quality of CAT ( M = 22 and 16) with the same tool.…”
Section: Discussionmentioning
confidence: 90%
“…The findings are then translated to the second stage where more stringent methodology such as RCTs is employed as a way of testing the efficacy of the intervention (Barkham & Mellor‐Clark, ). In the third stage, the treatment is implemented in settings that are closer to standard clinical practice to assess its effectiveness and external validity (Barkham & Mellor‐Clark, ; Calvert & Kellett, ).…”
Section: Introductionmentioning
confidence: 99%
“…The “hourglass model” is a recognized framework for supporting the appropriate stage development of treatments and therapies (Salkovskis, 1995) and has previously been used to evaluate a psychotherapy evidence base (see Calvert & Kellett, 2014 for an example). In stage 1 of the hourglass model, small practice-based treatment studies (e.g., small N designs) demonstrate proof of concept.…”
Section: Background and Aimsmentioning
confidence: 99%